EXTERNAL SOURCES OF FUND OF MICROFINANCE INSTITUTIONS (MFI) IN BANGLADESH: DO INSTITUTIONAL CHARACTERISTICS MATTER? - Islam, Serajul (Indian Journal of Finance and Banking, 2021)
The external sources of fund for the micro-finance institutions (MFIs) include various loans and donor’s fund. The loan financing consists of loan from the government, the loan from other micro credit financial institutions, the loan from the commercial bank and the loan from Palli Karma Sahayak Foundation (PKSF). There is the impact of capital resources on the profitability performance. Therefore, it is important for a firm to know about the significant influences of institutional characteristics on external sources of fund. Hence, this study investigates the driven factors of the sources of funds of microfinance institutions, the effect of institutional characteristics on sources of fund especially on external sources. The study is conducted by examining longitudinal data of 169 microfinance institutions (MFIs) from Bangladesh covering a period of six years from 2009 to 2014. This study employs relevant data from the Mix market and Microcredit Regulatory Authority (MRA) annual reports. Results show that a reliance on external sources of the fund (ESF) has a significant correlation with interest rate cap, inflation rate, ROA, number of branches (Size) and age of the MFIs. Donations have a significant correlation with the regularity variable and size of the MFIs. Additionally, apart from location, the rest of the institutional variables significantly influence the external sources of funds (ESF). JEL Classification Codes: G2, G21, G23, O16.